Human-Computer Interaction. Users and Applications 14th International Conference, HCI International 2011, Orlando, FL, USA, July 9-14, 2011, Proceedings, Part IV - Jacko, Julie A.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This four-volume set LNCS 6761-6764 constitutes the refereed proceedings of the 14th International Conference on Human-Computer Interaction, HCII 2011, held in Orlando, FL, USA in July 2011, jointly with 8 other thematically similar conferences. The revised papers presented were carefully reviewed and selected from numerous submissions. The papers accepted for presentation thoroughly cover the entire field of Human-Computer Interaction, addressing major advances in knowledge and effective use of computers in a variety of application areas. The papers of the fourth volume are organized in topical sections on HCI and learning, health and medicine applications, business and commerce, HCI in complex environments, design and usability case studies, children and HCI, and playing experience.
Keywords: Computer science; Information storage and retrieval systems; Information systems; Multimedia systems; Computer vision; Computer Science; User Interfaces and Human Computer Interaction; Information Systems Applications (incl.Internet).; Multimedia Information Systems; Information Storage and Retrieval; Computer Imaging, Vision, Pattern Recognition and Graphics; e-Commerce/e-business.